Haematological Changes in the Fresh Water Catfish Mystus vittatus Exposed to Sublethal Concentrations of Monocrotophos. - Sekhar, Dr.P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Effect of sublethal concentrations of Monocrotophos (4.5 ppm, 6.7 ppm and 13.5 ppm) on haematological parameters were studied in fresh water catfish Mystus vittatus. Monocrotophos toxicity resulted in a significant decrease in all the sub lethal concentrations and maximum at 13.5 ppm (RBC (-47), Hemoglobin content (-77), ESR(-75) and PCV % (-68) and a significant increase in WBC count (+55).